Pazopanib, a promising option for the treatment of aggressive fibromatosis. Issue 4 (April 2017) - Szucs, Zoltan; Messiou, Christina; Wong, Han Hsi; Hatcher, Helen; Miah, Aisha; Zaidi, Shane; van der Graaf, Winette T.A.; Judson, Ian; Jones, Robin L.; Benson, Charlotte
Abstract : Desmoid tumour/aggressive fibromatosis (DT/AF) is a rare soft-tissue neoplasm that is locally aggressive but does not metastasize. There is no standard systemic treatment for symptomatic patients, although a number of agents are used. Tyrosine kinase inhibitors have recently been reported to show useful activity. We reviewed our bi-institutional (Royal Marsden Hospital, Cambridge University Hospitals) experience with the tyrosine kinase inhibitor pazopanib in the treatment of progressing DT/AF. Eight patients with DT/AF were treated with pazopanib at Royal Marsden Hospital and Cambridge University Hospitals between June 2012 and June 2016. The median age of the patients was 37.5 (range: 27–60) years. The median duration of pazopanib treatment was 12 (range: 5–22) months and for three patients the treatment is ongoing. Three patients discontinued treatment early (patient preference, intolerable toxicity and logistical reasons, respectively). None of the patients showed radiological progression while on treatment, best responses according to Response Evaluation Criteria In Solid Tumors 1.1 were partial response in 3/8 and stable disease in 5/8 cases. Six patients derived clinical benefit from treatment in terms of improved function and/or pain reduction. Median progression-free survival was 13.5 (5–36) months. Only one patient experienced intolerable toxicity (grade 3 hypertension) leading to early treatment discontinuation. In our series of patients with DT/AF, pazopanib demonstrated important activity both in terms of symptom control (75%) and absence of radiological progression (100%). Results of ongoing confirmatory trials are eagerly awaited.